ARE LOCAL GOVERNMENTS OVERCONFIDENT WITH THE EFFECT OF BUDGET FORECAST ERRORS ON BUDGET DEVIATION? - Amor Marundha (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2020)
This study aims to examine the effect of budget forecast errors on budget deviations moderated by local governments’ overconfidence. The research sample used regency/city governments in Indonesia during the 2017-2019 period. The analysis tool uses Eviews version 10 and SPSS version 22. The results showed that budget forecast errors had a positive and significant effect on budget deviation, but the local government’s overconfidence cannot cause an effect of budget forecast errors on the budget deviation. Additional test results of this study also showed that regency/city governments who were overconfident tend to fail in controlling their budget which could cause a surplus or deficit compared to local governments that were not overconfident. The same conditions apply to budget forecast errors. This means that regency/city governments that are overconfident tend to estimate budgets that are too high for revenue and/or budget estimates that are too low for expenditure compared to local governments that are not overconfident. Consistent with the main test results, this study shows that budget forecast errors have a significant effect on budget deviation and tend to occur in the Central Indonesian region category. Furthermore, overconfident regency/city governments cannot moderate the effect of budget forecast errors on budget deviations. Finally, these findings indicate that there is no difference between the budget forecast errors and the budget deviation in the three categories of western, central, and eastern Indonesia.